Pathogenesis of lupus nephritis: RIP3 dependent necroptosis and NLRP3 inflammasome activation. (September 2019) - Guo, Chaohuan; Fu, Rong; Zhou, Mianjing; Wang, Shuang; Huang, Yuefang; Hu, Haoqiang; Zhao, Jijun; Gaskin, Felicia; Yang, Niansheng; Fu, Shu Man
Abstract: RIP3 activation leads to activation of necroptosis and the NLRP3 inflammasome pathways. The activation of RIP3 in lupus nephritis (LN) has not been investigated. In this study, RIP3 and necroptosis pathway activations were demonstrated in podocytes in renal biopsies from patients with class IV LN and in the diseased kidneys from lupus-prone NZM2328 and MRL/ lpr mice. RIP3 activation was accompanied with the activation of MLKL, the effector molecule of the necroptosis pathway, and activation of caspase-1, the effector of the NLRP3 inflammasome pathway. Podocyte activation of RIP3 was detected readily with the development of LN in NZM2328 mice, suggesting this activation may play a significant role in the pathogenesis of LN. GSK872, a RIP3 specific inhibitor, inhibited the development of LN in MRL/ lpr mice with down-regulation of RIP3 activation in podocytes, decreased the splenic sizes and weights and anti -dsDNA antibody titers. IgG from pooled sera of diseased NZM2328 mice succumbing to LN induced both the necroptosis pathway and NLRP3 inflammasome activation in a podocyte cell line and this activation was specifically blocked by GSK872. These results indicate that the necroptosis pathway and the RIP3 dependent NLRP3 inflammasome pathway are activated in podocytes during LN. Inhibition of RIP3 kinase may be a novel therapeutic approach to treat LN and systemic lupus erythematosus (SLE). Highlights: Necroptosis and NLRP3 inflammasome pathways are activated in podocytes in LN. RIP3 regulates both NLRP3 inflammasome and necroptosis activation. IgG from LN activates RIP3 dependent necroptosis and NLRP3 inflammasome pathways. Inhibition of RIP3 reduces autoimmunity and alleviates clinical manifestation of LN.